PEMBEKALAN TENTANG TIPS MEMILIH JURUSAN YANG SESUAI BAGI SISWA SMA BINAAN ASAK SATHORA - Miharni Tjokrosaputro (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
Many students are afraid to continue their education to the college level because they are unsure of which college degree is best for them. As a result, this community service initiative intends to assist ASAK-assisted underprivileged high school students in selecting the appropriate major for continuing their studies in college so that they might have a better future. The strategy employed in this activity is counseling to help impoverished high school students in the Kembangan area of West Jakarta choose majors of study. Zoom completed the deployment of this action on October 22, 2021. This community service program started with a debriefing about the differences between high school and college, followed by tips for choosing the right major for university degree and ended with a round of questions and answers. The output of this program is proceeding.